The Development of [Patient-Subj V-Qilai AP] as a Middle Construction in Chinese - Zhan, Fangqiong (Languages (Basel), 2025)
The middle construction (MC) is a term originally used to account for derived intransitives in the generative tradition and is well-documented in many Indo-European languages. While diverse views exist on the Chinese MC, some scholars have argued that Chinese [patient-subj V-qilai AP] sentences share traits with the English MC. Although diachronic literature on the development of the Chinese MC is limited, examining the grammaticalization of directional verb phrases like V-qilai provides valuable insights into its evolution. Building on previous analyses, I identify [patient-subj V-qilai AP] as the Chinese MC with V-qilai as its marker. Through an analysis of Classical Chinese data and the approach of constructional assemblies, I propose that the Chinese MC originated from assembled constructions comprising a subject, a directional verb phrase, and a descriptive construction. Over time, these assemblies evolved, with shifts in subject roles, motion interpretation, and descriptive functions, resulting in the emergence of the MC. Quantitative analysis of Classical data indicates the absence of the MC before 1900, suggesting its development through a gradual increase in the frequency of interconnected assemblies. By tracing the development of the Chinese MC, this research enhances our understanding of how middle voice mechanisms emerge across languages.